The world of Alexander in perspective : contextualizing Arrian - Rollinger, Robert; Degen, Julian (2022)
This volume is a collection of papers that have been given at an international conference in December 2019 in Bregenz, Austria. They focus on Arrian of Nicomedia's Anabasis Alexandrou which is our main source for the life and reign of Alexander the Great. So far, scholarship has paid only little attention to the Anabasis as literary cosmos of its own right. The various contributions critically evaluate the still extant general opinion, that Arrian deserves a distinguished status as the main source on the Macedonian conqueror since he allegedly closely followed his sources. But the first accounts of the participants in Alexander's famous expedition have only survived as fragments and thus their literary production is more or less shrouded in mystery. Hence, the tension between Arrian's literary creativity, propinquity to his sources, his relationship to his role-model Xenophon merits serious examination when assessing the value of his work as a historical source. The volume is the first attempt to contextualize the work of Arrian against various backdrops. This includes the reign of Alexander, the Classical and contemporary literary trends, the Second Sophistic as intellectual framework, the until yet neglected idea of "empire" as well as echoes and stimuli from the Achaemenid and Hellenistic period. The various contributions create a more complex image of Arrian as an author, his literary production and his idea of the Macedonian conqueror that helps us to gain a better understanding of this complex text and Alexander the Great as its protagonist